Histopathological Profile of Tumor and Tumor Like Lesions of Oral Cavity at A Tertiary Care Center in Nepal - Goyal, Binita; Sedhain, Mamata; Thapaliya, Prabha (Journal of College of Medical Sciences-Nepal, 2025)
Background Tumor and tumor like lesion of the oral cavity is any abnormal growth or mass with varied histopathological spectrum ranging from non-neoplastic reactive to benign to potentially malignant and malignant. Ulcero-proliferative lesions that can mimic cancer pose a diagnostic challenge. Final diagnosis can be made by histopathological examination. Methods This cross-sectional study was conducted on 148 cases of biopsies of oral cavity lesions received from January 2022 to December 2024. Lesions were categorized as non-neoplastic, benign, oral potentially malignant disorders (OPMD) and malignant. Age, gender, age group, site of lesion, category of lesion, clinical diagnosis and histopathological diagnosis were calculated. Association between category of clinical diagnosis and histopathological diagnosis was sought. Results Age of the patients ranged from 5 to 83 years with mean 42.9 years. Female male ratio was 1.02:1. The most common site was tongue comprising 43(29.1%) cases. 49(33.1%) cases were non-neoplastic, 24(16.2%) cases were benign, 55(37.2%) cases were OPMDs and 20(13.5%) cases were malignant. Mucocele was the most common non neoplastic lesion comprising 13(8.8%) cases. Squamous papilloma was the most common benign lesion comprising 7(4.7%) cases. Keratosis consistent with leukoplakia was the most common OPMD comprising 30(20.3%) cases and all 20(13.5%) malignant cases were squamous cell carcinoma. Conclusions Biopsy and histopathological examination serve as important tool in diagnosing or ruling out malignancy in tumor and tumor like lesions of oral cavity and guiding in further management.